Kompetensi Manajerial Kepala Sekolah dalam Mengelola Guru di SMKN se-Kota Pariaman - Putra, Kamilmar Haryadi; Adi, Nelfia (Journal of Practice Learning and Educational Development, 2023)
This research is motivated by problems related to the low managerial competency of school principals in managing teachers at SMKNs throughout Pariaman City. The formulation of the problem in this study is how is the managerial competency of the Principal in managing teachers at SMKNs throughout Pariaman City. This study aims to dig up information about the Managerial Competence of Principals in Managing Teachers at SMKNs throughout Pariaman City in terms of the aspects of coaching and professional development of teachers, utilization of teachers, giving rewards/awards, and motivating teachers. This type of research is descriptive quantitative. The study population was all teachers at SMKN in Pariaman City, totaling 346 people. A sample of 83 people was taken using a proportional stratified random sampling technique. The data collection instrument was a Likert scale model questionnaire with five answer choices, namely always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). This research questionnaire was tested on 30 people and processed using the SPSS 26.0.0 program, the results of the instrument were declared valid and reliable. Data analysis techniques use the average formula (mean). The results showed that the principal's managerial competence in aspects 1) coaching and professional development of teachers with an average score of 4.53 was in the capable category, 2) utilization of teachers with an average score of 4.39 was in the capable category, 3) giving rewards/awards with an average score of 3.95 was in the capable category, 4) motivating with an average score of 4.11 was in the capable category. Thus it can be concluded that the Managerial Competence of Principals in Managing Teachers at SMKNs throughout Kota Pariaman is in the capable category with an average score of 4.25. Based on these results, the authors suggest that the Managerial Competence of Principals in Managing Teachers in SMKNs throughout Pariaman City is maintained and needs to be increased again so as to improve the managerial competence of principals in managing teachers.